Media Campuran Tanah-Pasir dan Pupuk Anorganik untuk Memproduksi Inokulan Cendawan Mikoriza Arbuskula (CMA) - Iswandi Anas; J. L. O. Tampubolon (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
AMF fungi are obligate biotroph, they can not be multiplied on artificial growth medium. The growth of AMF fungi depends on photosynthates of the host plant. The AMF inoculant production so far is done on special growth media such as vermicullite or zeolite and using a certain composition of fertilizer such as Hyponex (N: P: K = 25: 5:20). The aims of this experiment were (1) to study the possibility of using soil-sand mixture for growth medium in AMF inoculant production, and (2) to study the possibility of using Urea, SP-36 and KCI as fertilizers in AMF inoculant production. The results of the experiment showed that soil-sand mixture was a better growth medium for AMF inoculant production than zeolite. The number of AMF fungi spore, the root infection rate and the root biomass of the host plant (shorgum) were higher on soil-sand mixture growth medium compared to zeolite. Urea, SP-36 and KCI can be used as subtitute to Hyponex fertilizer in AMF inoculant production. Key words: CMA, Produksi inokulum, Entrophospora colombiana. Glomus manihotis